Effects on Facial Growth Following Masseter Muscle Resection in Growing Rats—A Systematic Review - Georgia Kotantoula; Ioannis A. Tsolakis; Ioannis Lyros; Miltiadis A. Makrygiannakis; Christina Kanareli; Maria Dalampira; Apostolos I. Tsolakis (Animals, 2023)
An individual’s facial appearance is heavily influenced by facial symmetry. In the asymmetric mandible, periosteal apposition and endochondral ossification in one of the condyles may stimulate asymmetric growth of the body. Our aim was to review the impact on the growth following masseter resection. Relevant studies up to October 2022 were retrieved from PubMed, Scopus, and Web of Science. The PICOS method was utilized to determine eligibility, and the SYRCLE risk of bias tool was utilized to provide an estimate of potential bias. A predetermined algorithm was used to search the databases. The results of our systematic review of seven studies indicate that the masseter muscle strongly impacts craniofacial growth and development. Resection of the masseter muscle significantly reduces the sagittal and vertical development of the jaw in rats. In addition, the masseter muscle excision influences the mandibular morphology, including the condylar area, angle, and development direction of the jaw.